The Effect of Brand Image, Lifestyle, Electronic Word Of Mouth on Oppo Smartphone Purchase Decisions(Case study on Students in Semarang City) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This research aims to analyze the influence of brand image, lifestyle, and electronic word of mouth (eWOM) on the purchase decision of Oppo smartphones among students in Semarang City. This quantitative research uses an explanatory research design to explain causal relationships between variables. Data were collected through questionnaires distributed to 97 respondents selected using purposive sampling, focusing on students familiar with Oppo smartphones. Multiple regression analysis was used to test the proposed hypotheses. The findings reveal that brand image, lifestyle, and eWOM significantly and positively affect the purchase decision. The regression model accounts for 82.4% of the variation in purchase decisions, indicating a strong influence of the studied variables.
Keywords: Brand Image, Lifestyle, Electronic Word of Mouth, Purchasing Decisions